Management conflict in venture capital financing: A study on the Malaysian venture capital companies - Mohammad, Hisham; Minai, Mohd Sobri; Lucky, Esuh Ossai-Igwe (2013)
The increasing complexity of managing venture business has made it necessary for Malaysian venture capitalists to develop cordial relationships with the entrepreneurs in order to achieve mutual goal.However, the warm venture cooperation built between venture capitalists and entrepreneurs may still be interrupted by management conflict which occurred due to various managerial factors. Thus, conflict becomes one of the major barriers that may prevent both venture capitalists and entrepreneurs from creating successful venture business.As a result, this study investigates the management conflict in venture capital investments and the possible resolutions for the conflict.Due to this, a cross-sectional study of questionnaire survey research design was conducted in this respect.Questionnaire data were generated from 35 Malaysian venture capital companies located in Kuala Lumpur and Selangor. The questionnaires were distributed through mailing procedure.Overall, the findings indicate that the managerial factors significantly influence the management conflict.Further results show that managerial factors which consist of Deal Origination and Screening (DOS), Evaluating Venture Proposal (EVP), Contracting and Deal Structuring (CDS), Monitoring and Post Investment Activities (MPI) and Risk Management (RM) significantly influence the management conflict in venture cooperation.Based on the findings, it is inferred that managerial factors does influence the occurrence of management conflict in venture cooperation. Thus, the study recommends that Malaysian venture capitalists, which includes policy makers, to give more consideration to the managerial factors in order to reduce the possibility of conflict to occur.Finally, both the theoretical and practical implications are duly presented as well as that of the limitations of the study and suggestions for future study are included in this regard.